2017
DOI: 10.1111/ene.13274
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain in cerebrospinal fluid and prediction of disease activity in clinically isolated syndrome and relapsing–remitting multiple sclerosis

Abstract: This study demonstrates the potential prognostic value of NFL in baseline CSF in CIS and relapsing-remitting MS and supports its use as a predictive biomarker of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 32 publications
6
92
1
6
Order By: Relevance
“…The evaluation of sNfL is a promising opportunity to evaluate MS disease activity. While measurement of NfL in CSF has already demonstrated a significant correlation with inflammatory disease activity, [12][13][14] fourth-generation immunoassays allow the implementation of sNfL measurement from patients`blood as "easy-to-measure" marker to reflect acute neuroaxonal damage. Of particular interest is the proof that sNfL levels can be used to separate not only patients with MS from healthy controls but also to separate patients with MS with and without persistent clinical and subclinical MRI disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of sNfL is a promising opportunity to evaluate MS disease activity. While measurement of NfL in CSF has already demonstrated a significant correlation with inflammatory disease activity, [12][13][14] fourth-generation immunoassays allow the implementation of sNfL measurement from patients`blood as "easy-to-measure" marker to reflect acute neuroaxonal damage. Of particular interest is the proof that sNfL levels can be used to separate not only patients with MS from healthy controls but also to separate patients with MS with and without persistent clinical and subclinical MRI disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reappearance of disease activity, ATZ retreatment was initiated in 8 patients (figures 3-5, patient [8][9][10][11][12][13][14][15]. At least, 10 ATZ retreatments (7 patients received 1 ATZ retreat and 1 patient received 3 ATZ retreats) had to be performed in our cohort.…”
Section: Snfl After Atz Retreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 NfL are released upon axonal or neuronal damage or degeneration, and can be found as a consequence, in the CSF and blood. Prior studies have shown that NfL concentrations in cerebrospinal fluid (CSF) are associated with the occurrence of MRI lesions, relapses, neurological disability, and treatment status in MS. [4][5][6][7] Additional studies have demonstrated predictive value of CSF neurofilament light or heavy chain levels with clinical outcomes, [8][9][10] and MRI measures. 11 More recently, single molecule array (SIMOA) based assays, which offer improved sensitivity for detection of molecules, have been used to measure NfL in serum samples.…”
Section: Introductionmentioning
confidence: 99%
“…These structural elements have been shown to accumulate secondary to aberrant phosphorylation and disruption of slow axonal transport (9,18,26,42). Interestingly, increased levels of neurofilaments have been found in the CSF of patients with multiple neurodegenerative diseases and are thought to correspond to axonal damage (15,30,43). Non-useful proteins are marked by ubiquitin for degradation by the ubiquitin protease system (UPS) (3).…”
Section: Discussionmentioning
confidence: 99%